Two Objective Public Service System Design Problem - Janáček, Jaroslav; Koháni, Michal; Grygar, Dobroslav; Fabricius, René (Communications - Scientific Letters of the University of Zilina, 2021)
The  public  service  system  serves  population  spread  over  a  geographical  area from a given number of service centers. One of the possible approaches to  the  problem  with  two  or  more  simultaneously  applied  contradicting  objectives  is  determination  of  the  so-called  Pareto  front,  i.e.  set  of  all  the  feasible non-dominated solutions. The Pareto front determination represents a crucial computational deal, when a large public service system is designed using  an  exact  method.  This  process  complexity  evoked  an  idea  to  use  an  evolutionary  metaheuristic,  which  can  build  up  a  set  of  non-dominated  solution  continuously  in  the  form  of  an  elite  set.  Nevertheless,  the  latter  approach does not assure that the resulting set of solutions represents the true Pareto front of the multi-objective problem solutions. Within this paper, authors  deal  with  both  approaches  to  evaluate  the  difference  between  the  exact and heuristic approaches.
Keywords: service system; multi-objective; Pareto front; exact approach; genetic algorithm